Production and stably maintenance of strigolactone by transient expression of biosynthetic enzymes in Nicotiana benthamiana - Yata, Akira; Nosaki, Shohei; Yoda, Akiyoshi; Nomura, Takahito; Miura, Kenji (Frontiers in Plant Science, 2022)
Strigolactones (SLs) are phytohormones that play an essential role in plant–microbe interactions. The instability of SLs makes it challenging to use them for application to agriculture. In this study, we successfully produced a large amount of the 4-deoxyorobanchol (4DO), one of SLs, in the leaves of Nicotiana benthamiana, using a transient expression system to express SL biosynthetic enzymes. Using this system, the yield of 4DO was 2.1 ± 0.3 μg/gFM (fresh mass). Treatment of leaves at 80 °C for 16 h killed Agrobacterium and approximately half amount of 4DO was left in the leaves (1.0 μg/gFM (calculated based on the original FM) ± 0.3). Interestingly, incubation of dried leaves at room temperature for 1 month maintained an almost equal amount of 4DO (0.9 ± 0.2 μg/gFM) in the leaves. These results suggest that high accumulation of 4DO with stability for long periods can be achieved in plant leaves.